2020
DOI: 10.1017/s0007114520004742
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet in mice alters immune regulation and lung function in the offspring

Abstract: Polyunsaturated fatty acids (PUFA) modulate immune function and have been associated with risk of childhood atopy and asthma. We investigated the effect of maternal fat intake in mice on PUFA status, elongase and desaturase gene expression, inflammatory markers and lung function in the offspring. C57BL/6J mice (n=32) were fed either standard chow (C, 21% kcal fat) or a high fat diet (HFD, 45% kcal fat) for 4 weeks prior to conception and during gestation and lactation. At 21 days of age, offspring were weaned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Moreover, dietary nutrient supplementation during pregnancy and lactation also improved growth performance and altered offspringʼs immunity and gut microbiota. 5,7,25 Therefore, the present study evaluated the effects of betaine hydrochloride addition in sow diets during gestation and lactation on plasma immune function, intestinal morphology, and intestinal microbiota and their metabolites in suckling piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dietary nutrient supplementation during pregnancy and lactation also improved growth performance and altered offspringʼs immunity and gut microbiota. 5,7,25 Therefore, the present study evaluated the effects of betaine hydrochloride addition in sow diets during gestation and lactation on plasma immune function, intestinal morphology, and intestinal microbiota and their metabolites in suckling piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that maternal HFD can affect the lung and somatic growth of the offspring. The lung volume and morphology of the offspring were affected by in utero exposure to maternal inflammation, which was mainly induced by metabolic dysfunction under maternal HFD and independent of inflammation in individual offspring (Smoothy Maternal diet composition may be more important than maternal obesity (Losol et al, 2021). During lactation, maternal HFD can cause offspring to gain weight.…”
Section: Offspring Asthma In Maternal Obese Micementioning
confidence: 99%
“…Other studies have indicated that maternal HFD can alter offspring’s plasma and hepatic fatty acid composition, secrete inflammatory markers, and modify lung development. Maternal diet composition may be more important than maternal obesity ( Losol et al, 2021 ). During lactation, maternal HFD can cause offspring to gain weight.…”
Section: Immune Responses In the Different Obesity-related Asthma Mou...mentioning
confidence: 99%
“…Microbiota metabolites may influence the development of allergic outcomes through the direct immunomodulatory or immune metabolic effects 6 or through the induced changes in the composition of gut microbiota 7 . It is established that the early‐life dysbiosis in the gut microbial composition might eventually lead to asthma and allergy, 8,9 which is why an increase in alpha diversity after consumption of fermented foods might be a very promising strategy in the context of prevention and treatment of atopic diseases. Although high‐fiber diet did not reveal any significant changes in microbial diversity, there was an increased level of commensal Lachnospira when compared to high‐fermented diet.…”
Section: Figurementioning
confidence: 99%